Squirrels as Green Allies to Human Resource Development Agenda on Pro-environmental Practices as the Fangs of Climate Change Rages on - Osolase, Ehikioya Hilary; Mohd Rasdi, Roziah; Dato' Mansor, Zuraina (Universitas Negeri Padang, 2025)
Through a process known as “zoochory, scatter hoarding, or caching”, a squirrel gathers approximately about 10,000 nuts during the autumn season and have them kept underground. With 95% possibility that the exact location were the seeds are concealed will be forgotten. As a result of its forgetfulness, squirrels often repeat these activities unending. These seeds which have been forgotten by the squirrels, sprouts and successively become a woodland regeneration with green trees that protects the natural environment which continuously renews the ecosystem. Hence, squirrels can be labelled as “green allies to the agenda of human resource development (HRD) scholars/practitioners”, as both utilizes its capabilities in advancing pro-environmental practices among humans across different sectors and industries as well as the larger society. In addition, collaborating with researchers from other fields (e.g. environmental sciences, business management, and varied social sciences, etc.), will propel HRD scholars to deploy the behavioral component of squirrels in promoting eco-friendly practices among the workforce in organizations, including the wider society. The connection between squirrels’ green attitude and HRD’s initiatives on pro-green practices, reveals a mutualistic interaction between squirrels and HRD scholars/practitioners’ expertise on ecofriendly practices. With the discussions provided on the symbiotic relationship between squirrels’ pro-environmental behaviors and HRDs expertise for promoting green practices, the research question was answered. Finally, using the three steps (unfreeze-change-refreeze) of Lewin’s change theory which is acknowledged as an HRD change mechanism, a research framework was developed, along with providing directions for cross-disciplinary research and theory advancement and building